2017
DOI: 10.5964/ejop.v13i1.1248
|View full text |Cite
|
Sign up to set email alerts
|

Believing is doing: Emotion regulation beliefs are associated with emotion regulation behavioral choices and subjective well-being

Abstract: Research in emotion regulation has begun to examine various predictors of emotion regulation choices, including individual differences and contextual variables. However, scant attention has been paid to the extent to which people’s beliefs about the specific consequences of emotion regulation strategies for the components of an emotional response and long-term well-being predict their behavioral regulatory choices and, in turn, their subjective well-being. Participants completed measures to assess their belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
(72 reference statements)
1
16
0
2
Order By: Relevance
“…Specifically for anxiety-eliciting situations, it is possible that women are less motivated to downregulate anxiety by means of cognitive reappraisal, since they are more prone to feelings of anxiety (e.g., McLean and Anderson, 2009 ) and are thus more likely to accept these feelings as part of their everyday lives. Complementing this assumption, despite good reappraisal capacity, women might also be less convinced of the effectivity of cognitive reappraisal in reducing their anxious feelings, which adds beliefs about consequences of cognitive reappraisal as another potential influencing factor (e.g., Ortner et al, 2017 ). Our data, however, can only partly support all these arguments, because we did not assess efforts put in the reappraisal task, beliefs in reappraisal effectiveness, and the preferred use of cognitive reappraisal as a trait (e.g., Gross and John, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically for anxiety-eliciting situations, it is possible that women are less motivated to downregulate anxiety by means of cognitive reappraisal, since they are more prone to feelings of anxiety (e.g., McLean and Anderson, 2009 ) and are thus more likely to accept these feelings as part of their everyday lives. Complementing this assumption, despite good reappraisal capacity, women might also be less convinced of the effectivity of cognitive reappraisal in reducing their anxious feelings, which adds beliefs about consequences of cognitive reappraisal as another potential influencing factor (e.g., Ortner et al, 2017 ). Our data, however, can only partly support all these arguments, because we did not assess efforts put in the reappraisal task, beliefs in reappraisal effectiveness, and the preferred use of cognitive reappraisal as a trait (e.g., Gross and John, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the meta-emotional problem is considered to play a role in affective disorders. Indeed, depressive rumination, a key risk factor for clinical depression, is related to negative thinking about depressive symptoms ( Nolen-Hoeksema, 1991 , 2000 ) and fear of depressed mood and anxiety was associated with rumination and emotional avoidance ( Trincas et al, 2016 ). Strikingly, this study revealed that the tendency to have a negative secondary reaction to distress, as measured by the Non-Acceptance subscale of the Difficulty in Emotion Regulation Scale ( Gratz and Roemer, 2008 ), was strongly correlated with higher negative beliefs about emotions (i.e., that emotions are irrational).…”
Section: Authors’ Hypothesismentioning
confidence: 99%
“…Strikingly, this study revealed that the tendency to have a negative secondary reaction to distress, as measured by the Non-Acceptance subscale of the Difficulty in Emotion Regulation Scale ( Gratz and Roemer, 2008 ), was strongly correlated with higher negative beliefs about emotions (i.e., that emotions are irrational). Moreover, this idea was associated with feelings of guilt, shame, embarrassment, and weakness in reaction to emotional experience ( Trincas et al, 2016 ). In line with this finding, it has been observed that feeling ashamed and humiliated for having PTSD or guilty about intrusive thoughts in OCD are predictors of poor therapy outcomes ( Gilbert and Andrews, 1998 ; Clohessy and Ehlers, 1999 ) because patients avoid seeking treatment or engaging in exposure ( Leahy, 2007 ).…”
Section: Authors’ Hypothesismentioning
confidence: 99%
“…Emotion regulation, known as the ability to regulate emotions in order to succeed, has been a widely studied subject during the last three decades [26] that has emerged as one of the pillars of well-being and social functioning [27][28][29][30][31][32][33]. According to a process model of emotion regulation, emotions may be regulated in five points along the emotion generative process: (1) selection of the situation, (2) modification of the situation, (3) deployment of attention, (4) change of cognitions (meanings) and (5) modulation of the experiential, behavioral or physiological responses.…”
Section: Introductionmentioning
confidence: 99%